IMF Staff papers, Volume 45 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1998)
This paper presents international evidence on the determinants of trade dynamics. It provides some new empirical perspectives on the relationship between international trade and macroeconomic fluctuations in industrial economies. A comprehensive set of stylized facts concerning fluctuations in trade variables and their determinants is presented. A measure of the quantitative importance of international trade for the propagation of domestic business cycles is then constructed, focusing on the role of external trade as a catalyst for cyclical recoveries.